2011
DOI: 10.1093/rpd/ncr344
|View full text |Cite
|
Sign up to set email alerts
|

Risk estimates for meningiomas and other late effects after diagnostic X-ray exposure of the skull

Abstract: This study aims to investigate the contribution of diagnostic exposures to the rising rates of brain tumours and other neoplasms which are observed in several industrial nations. Included are benign tumours in the head and neck region and cataracts which are neglected in usual risk estimates by international and national radiation protection committees. Dose-effect relationships for tumours of the brain, skin, thyroid and other sites of the head region, leukaemia and cataracts are taken from the literature. Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…concentration and blood ethyl alcohol concentration were measured before and after liberately drinking alcohol. The study was approved by the local Ethics Committee of the In der Notfallsituation wird vom Unfallchirurgen erwartet, dass er das Patientenrisiko durch Strahlenbelastung im Rahmen der cCT [7,8] gegen die zu erwartende Aussagekraft der cCT abwägt und entsprechend entscheidet. Um diese Entscheidung von der Erfahrungsebene unabhängig zu machen, wurden verschiedene Biomarker untersucht, um Patienten auf erhebliche Hirnschäden zu untersuchen [9 -12].…”
Section: Introductionunclassified
“…concentration and blood ethyl alcohol concentration were measured before and after liberately drinking alcohol. The study was approved by the local Ethics Committee of the In der Notfallsituation wird vom Unfallchirurgen erwartet, dass er das Patientenrisiko durch Strahlenbelastung im Rahmen der cCT [7,8] gegen die zu erwartende Aussagekraft der cCT abwägt und entsprechend entscheidet. Um diese Entscheidung von der Erfahrungsebene unabhängig zu machen, wurden verschiedene Biomarker untersucht, um Patienten auf erhebliche Hirnschäden zu untersuchen [9 -12].…”
Section: Introductionunclassified
“…The best known epidemiological evidence comes from studying the effect of ionizing radiation on Israeli children, between 1948 and 1960, whose scalps were irradiated for tinea capitis and later showed a 10-fold increase in the incidence of meningiomas 28. Other reports have come from full mouth x-ray studies for dental diagnosis,29–31 diagnostic x-ray exposure of the skull,19 and cranial irradiation for tumor treatment 27 29. Hence cranial exposure has been a major concern for the diagnostic and interventional radiologist.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Berrington et al 40 estimated mean lifetime cancer risk is 0.04% to 0.09% per head CT, utilizing BEIR VII data and age- and sex-specific scan frequencies. Pflugbeil et al 38 reported an induced incidence of 0.24 brain tumors per 1000 CT scans in children annually, using epidemiological data and studies of neoplasm induction after radiotherapy to model risk. Chodick et al 43 applied Brenner et al’s 8 method to estimate cancer mortality attributable to CT examinations in patients under 18 years of age and projected the annual number of excess lifetime cancer deaths attributable to pediatric CT to be highest in the youngest children (0.48 for girls, 0.78 for boys), declining with age.…”
Section: Resultsmentioning
confidence: 99%